Analysis of Reading Interest Among Adolescents in The Digital Age (A study at Sman 4 Bogor) - Insan, Syahrul Maulana; Mintarti, Mintarti; Lestari, Soetji (Indonesian Journal of Digital Society is a scientific journal, 2026)
This study aims to identify factors that may enhance adolescents’ reading interest amid the current digital transformation. Conducted at SMAN 4, Bogor City, West Java, the research employs a descriptive-quantitative method with a proportionate random sampling technique. The sample includes 152 students drawn from a total population of 635. The findings reveal that education and parental involvement play pivotal roles in fostering reading interests, highlighting the profound impact of socialisation on individual behaviour. Furthermore, the study indicates that students’ reading preferences have expanded beyond traditional printed books to various digital platforms, such as web articles, digital comics, and social media. Finally, the results suggest that students’ habitus deeply influences the formation of reading interest. At the same time, advances in technology and the internet have fundamentally altered how high schoolers access and engage with literary resources.